Design and validation of the Regional Anaesthesia Procedural Skills Assessment Tool1. (December 2015) - Chuan, A.; Graham, P. L.; Wong, D. M.; Barrington, M. J.; Auyong, D. B.; Cameron, A. J. D.; Lim, Y. C.; Pope, L.; Germanoska, B.; Forrest, K.; Royse, C. F.
Summary: The aim of this study was to create and evaluate the validity, reliability and feasibility of the Regional Anaesthesia Procedural Skills tool, designed for the assessment of all peripheral and neuraxial blocks using all nerve localisation techniques. The first phase was construction of a 25‐item checklist by five regional anaesthesia experts using a Delphi process. This checklist was combined with a global rating scale to create the tool. In the second phase, initial validation by 10 independent anaesthetists using a test–retest methodology was successful (Cohen kappa ≥ 0.70 for inter‐rater agreement, scores between test to retest, paired t‐test, p > 0.12). In the third phase, 70 clinical videos of trainees were scored by three blinded international assessors. The RAPS tool exhibited face validity (p < 0.026), construct validity (p < 0.001), feasibility (mean time to score < 3.9 min), and overall reliability (intraclass correlation coefficient 0.80 (95% CI 0.67–0.88)). The Regional Anaesthesia Procedural Skills tool used in this study is a valid and reliable assessment tool to score the performance of trainees for regional anaesthesia.